Railway efficiency: An overview and a look at opportunities for improvement - Arne Beck; Heiner Bente; Martin Schilling (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
Railway efficiency is a topic of interest worldwide for railway managers operating in competitive markets and for fiscally strained governments. Several recent studies indicate that European railways differ in terms of their efficiency. Based on a comparison with some major non-European railway systems, our analysis provides further evidence that significant efficiency gaps exist.
Keywords: 330